2000
DOI: 10.1002/(sici)1099-0682(200002)2000:2<359::aid-ejic359>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Metal-Stabilized α-CF3-Carbenium Ion Complexes under Mild Conditions: Synthesis, Structures, and Reactivity

Abstract: Complexed α‐CF3 propargyl alcohols of the general formula [(M2L6){μ‐η2,η2‐RC≡CCH(CF3)(OH)}] were prepared with M2L6 = Co2(CO)6, R = CH3(CH2)4– (1), R = C6H5– (2); M2L6 = Co2(CO)5P(C6H5)3, R = CH3(CH2)4– (3a,b), R = C6H5– (4a,b); M2L6 = Co2(CO)4dppm, R = C6H5– (5); M2L6 = Co(CO)3MoCp(CO)2, R = CH3(CH2)4– (6a,b), R = C6H5– (7a,b). An X‐ray molecular structure of the propargyl‐alcohol complex [{Co2(CO)4dppm}{μ‐η2,η2‐C6H5C≡CCH(CF3)(OH)}] (5) was also determined. The related carbenium ions [(M2L6){μ‐η2,η3‐RC≡CCH(CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Ultimately, this should be improved by deliberately changing the two phenyl substituents for substituents exerting opposite mesomeric or inductive acceptor destabilization (–M or –I effect; the more or less protecting groups are denoted as PG in Scheme 1 ). Within this prospect, trifluoromethyl groups are ideal candidates: 13 it was indeed observed that the quite general method for the conversion of 1,4-dioxybut-2-yne derivatives to the corresponding butatrienes by treatment with SnCl 2 /HCl is not compatible with CF 3 substituents. 6 c Two substituents PG = CF 3 at adjacent carbinoxy vertices of a hexaoxy-[6]pericyclyne D F are therefore anticipated to freeze the reactivity of corresponding 1,4-dioxybut-2-yne edge towards reduction and thus optimize the selectivity for the partly reduced carbo -cyclohexadiene product C F vs. the putative carbo -benzene A F ( Scheme 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, this should be improved by deliberately changing the two phenyl substituents for substituents exerting opposite mesomeric or inductive acceptor destabilization (–M or –I effect; the more or less protecting groups are denoted as PG in Scheme 1 ). Within this prospect, trifluoromethyl groups are ideal candidates: 13 it was indeed observed that the quite general method for the conversion of 1,4-dioxybut-2-yne derivatives to the corresponding butatrienes by treatment with SnCl 2 /HCl is not compatible with CF 3 substituents. 6 c Two substituents PG = CF 3 at adjacent carbinoxy vertices of a hexaoxy-[6]pericyclyne D F are therefore anticipated to freeze the reactivity of corresponding 1,4-dioxybut-2-yne edge towards reduction and thus optimize the selectivity for the partly reduced carbo -cyclohexadiene product C F vs. the putative carbo -benzene A F ( Scheme 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…While the tertiary carbenium ion 108 was isolable as a solid [ 83 84 ], the tertiary carbenium ion 109 and the secondary derivatives 112a – c and 113a , b afforded oils. The secondary derivatives were much more sensitive in spite of the use of electron-rich Co–Mo clusters and could only be characterized by NMR and IR spectroscopy [ 85 ]. Upon ionization, the change in the electronic density is directly reflected by the downfield shift of the 19 F NMR chemical shift of the CF 3 group but also by a CO shift to a higher frequency.…”
Section: Reviewmentioning
confidence: 99%
“…10 5 times less reactive (E = -6.71), indicating insufficient reactivity with the less reactive allylsilanes and all but the most electron rich arenes. The reactivity of dppm complexes is less certain, as pK R+ values (-11.0) suggest a cation less stable than the hexacarbonyl complexes [18], while work on CF 3 substituted propargylium complexes suggest greatly enhanced cation stability with this ligand [19]. Propargyl cations with one and two tris(pyrrolyl)phosphine ligands have also been generated [20]; although these cations are attacked by one of the pyrrole ligands, it is not possible at this time to evaluate cation's properties in electrophilicity or pK R+ terms.…”
Section: Fundamental Propertiesmentioning
confidence: 99%
“…In many of these cases use of a precursor propargyl chloride complex and AgBF 4 are the recommended choices for generation of these formally umpolung, carbonyl γ -cation equivalents. Strongly electronwithdrawing CF 3 groups have been tolerated at the propargylic centre (10), most reliably when the centre also possesses an aryl substituent [19,25]. Without the aryl groups, attempted cation formation fails, but replacement of one CO by triphenylphosphine or two CO's by a dppm ligand allows cation formation in these cases.…”
Section: Reactivitymentioning
confidence: 99%
See 1 more Smart Citation